EXPLORING THE FACTORS AND LEVELS OF STUDENTS’ AUTONOMY IN LANGUAGE LEARNING - Wiranti, Sukma; Widiyati, Elok (IJIET (International Journal of Indonesian Education and Teaching), 2023)
Students’ autonomy is important in language learning since students’ autonomy is considered one of the elements in successful language learning. This study aimed to explore the students’ autonomy levels in language learning by considering the characteristics of autonomous students and the factors that affected students’ autonomy. As a mixed-method study, this study combined questionnaires and interviews as the instruments. The sample of this research was 34 students of XII MIPA 1 of SMA Negeri 2 Semarang. The quantitative data regarding students’ autonomy levels showed: emerging (0%), beginning (14.12%), intermediate (57.60%), and advanced (28.28%). It indicated that the majority of the students’ autonomy level in language learning is considered at the intermediate level. While the mean of quantitative data regarding the factors influencing students’ autonomy showed: students’ role (21.13%), teacher’s role (21.83%), task (16.90%), environment (21.83%), material (18.31%). It indicated that students agreed that students’ autonomy was influenced by those supporting factors. The qualitative data revealed that the students’ autonomous skills were also supported by several factors, such as students’ goals and motivation, teacher and students’ bond, learning materials and activities, and a supportive learning environment.